A novel, long-acting glucagon-like peptide receptor-agonist: dulaglutide - Gurung T (Dove Medical Press, 2015)
Tara Gurung,1 Deepson S Shyangdan,1 Joseph Paul O’Hare,2 Norman Waugh1 1Warwick Evidence, 2Division of Metabolic and Vascular Health, Warwick Medical School, University of Warwick, Coventry, UK Background: Dulaglutide is a new, long-acting glucagon-like peptide analogue in the treatment of type 2 diabetes. It is available in two doses, 0.75 and 1.5 mg, given by injection once weekly. This systematic review reports the effectiveness and safety of dulaglutide in type 2 diabetes in dual and triple therapy.Methods: MEDLINE, MEDLINE In-Process and Other Non-Indexed Citations, EMBASE, and conference abstracts were searched from 2005 to August 2014, and updated in January 2015. Company websites and references of included studies were checked for potentially relevant studies. European Medicines Agency and US Food and Drug Administration websites were searched.Results: Four trials were included. All were manufacturer-funded randomized controlled trials from the Assessment of Weekly Administration of Dulaglutide in Diabetes (AWARD) program. AWARD-1 compared dulaglutide 1.5 mg against exenatide 10 µg twice daily and placebo, AWARD-2 compared dulaglutide 0.75 and 1.5 mg against insulin glargine, AWARD-5 compared dulaglutide 0.75 and 1.5 mg against sitagliptin 100 mg and placebo, and AWARD-6 compared dulaglutide 1.5 mg against liraglutide 1.8 mg. The duration of follow-up in the trials ranged from 26 to 104 weeks. The primary outcome of all the included trials was change in HbA1c. At 26 weeks, greater HbA1c reductions were seen with dulaglutide than with twice daily exenatide (dulaglutide 1.5/0.75 mg: −1.5%/−1.3%; exe: 0.99%) and sitagliptin (1.5/0.75 mg −1.22%/−1.01%; sitagliptin: −0.6%). HbA1c change was greater with dulaglutide 1.5 mg (−1.08%) than with glargine (−0.63%), but not with dulaglutide 0.75 mg (−0.76%). Dulaglutide 1.5 mg was found to be noninferior to liraglutide 1.8 mg. More patients treated with dulaglutide achieved HbA1c targets of <7% and ≤6.5%. Reduction in weight was greater with dulaglutide than with sitagliptin and exenatide. Hypoglycemia was infrequent. The main adverse events were nausea, diarrhea, and vomiting.Conclusion: Dulaglutide is effective in the treatment of patients with type 2 diabetes but we need long follow-up data for safety concerns.Keywords: dulaglutide, glucagon-like peptide analogue, type 2 diabetes, effectiveness, glycemic control